ENERGY-EFFICIENT MATERIALS IN BUILDINGS AND STRUCTURES: TECHNOLOGIES AND TRENDS - Nabiyev , M.; Abobakirov, A. (Innovative Development in Educational Activities, 2023)
This article presents an in-depth exploration of energy-efficient materials used in buildings and structures. It provides an overview of the latest technologies and trends in the integration of energy-efficient materials, emphasizing their impact on reducing energy consumption, environmental sustainability, and cost-effective construction practices.